Women's Trafficking Portrayed in The Film Gangubai Kathiawadi - Eka Putri, Stevanie Alexandra (LITERA KULTURA : Journal of Literary and Cultural Studies, 2024)
This study analyzes women's trafficking in the Bollywood film "Gangubai Kathiawadi" (2022). The main focus of this study is the main character's experience as a victim of trafficking and how to deal with the situation. Through Spivak's feminist postcolonial theory, specifically the concept of the subaltern, the results showed that the main character experienced marginalization and injustice due to male gender views, which led to being trafficked and not heard as part of the subaltern. In dealing with this situation, the main character goes through a process of agency and resistance. This study concludes that the film portrays women trapped in human trafficking as subalterns who experience marginalization and try to overcome the situation.